Restructuring of coal mines: information resources - Sapytska, Iryna (Skhid, 2015)
Coal is a strategic resource for Ukraine and it is therefore necessary to identify some promising directions for development of mines within the Donetsk coal basin, despite economic and political difficulties. Restructuring plays an important role in improvement of coal enterprises' performance. In her previous publication, the author proposed a coal mine restructuring model which included some technological changes, with information resources being their important element. Computer technology facilities enable mine managers and specialists to obtain reliable, complete and timely information required for taking managerial decisions. The research conducted allowed to identify two main directions for process informatization and automation: technology and management. The technological direction implies equipping coal mining complexes with automated monitoring and control systems. As an example, the author examines functions of a Technologist's Automated Information System (AIST) which collects, processes, transfers and provides necessary information about the longwall operation. Labor safety of miners is an integral part of the coal mining process. To improve its level, there are integrated safety systems in place. The paper describes the UTAS (Unified Telecommunication System for Dispatch and Automated Controls of Mining Machines and Technological Complexes) and ITRAS (International Transportation System) and their benefits. The managerial direction is represented by a SKIP computer support system which performs information computation operations. The conducted analysis of information support of production and managerial activities shows that the restructuring necessitates improved informatization of the above processes. Towards that end, it is proposed to introduce the main modules of the SAMARA geoinformation system, which help develop, update and employ an information and geometric model of a mine take for addressing design, calculation and graphical tasks. To improve quality of administrative efforts of accounting and personnel departments, it is expedient to use Module '1С: Wages and staff' of software '1С: Enterprise'.